Authority and Incentives in Organizations - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
The paper analyzes how the choice of organizational structure leads to the best compromise between controlling behavior based on authority rights and minimizing costs for implementing high efforts. Concentrated delegation and hierarchical delegation turn out to be never an optimal compromise. If the CEO is more efficient than the division heads (i.e., the CEO's costs from exerting high effort are smaller than those of the division heads), the owner will prefer full delegation to the divisions to replace high incentive pay for motivating the division heads by incentives based on private benefits of control. In that situation, the importance of cooperative behavior between the firm's divisions determines whether decentralization or cross-authority delegation is the optimal form of full delegation. If, however, the division heads are more efficient than the CEO, then centralization or partial delegation can also be optimal.
Keywords: D21; D23; D86; L22; 330; authority; centralization; contracts; decentralization; moral hazard